Inhibition of human recombinant T‐type calcium channels by phytocannabinoids in vitro. (26th April 2022) - Mirlohi, Somayeh; Bladen, Chris; Santiago, Marina J.; Arnold, Jonathon C.; McGregor, Iain; Connor, Mark
Abstract : Background and Purpose: T‐type Ca channels ( I Ca ) regulate neuronal excitability and contribute to neurotransmitter release. The phytocannabinoids Δ 9 ‐tetrahydrocannabinol and cannabidiol effectively modulate T‐type I Ca, but effects of other biologically active phytocannabinoids on these channels are unknown. We thus investigated the modulation of T‐type I Ca by low abundance phytocannabinoids. Experimental Approach: A fluorometric (fluorescence imaging plate reader [FLIPR]) assay was used to investigate modulation of human T‐type I Ca (CaV 3.1, 3.2 and 3.3) stably expressed in FlpIn‐TREx HEK293 cells. The biophysical effects of some compounds were examined using whole‐cell patch clamp recordings. Key Results: In the FLIPR assay, all 11 phytocannabinoids tested modulated T‐type I Ca, with most inhibiting CaV 3.1 and CaV 3.2 more effectively than CaV 3.3. Cannabigerolic acid was the most potent inhibitor of CaV 3.1 ( p IC50 6.1 ± 0.6) and CaV 3.2 ( p IC50 6.4 ± 0.4); in all cases, phytocannabinoid acids were more potent than their corresponding neutral forms. In patch clamp recordings, cannabigerolic acid inhibited CaV 3.1 and 3.2 with similar potency to the FLIPR assay; the inhibition was associated with significant hyperpolarizing shift in activation and steady‐state inactivation of these channels. In contrast, cannabidiol, cannabidivarin, and cannabigerol only affected channel inactivation. Conclusion and Implications: Modulation of T‐type calcium channels is a common property of phytocannabinoids, which all increase steady‐state inactivation at physiological membrane potentials, with some also affecting channel activation. Thus, T‐type I Ca may be a common site of action for phytocannabinoids, and the diverse actions of phytocannabinoids on channel gating may provide insight into structural requirement for selective T‐type I Ca modulators.